2009
DOI: 10.1007/s00455-009-9227-y
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Heavy-Chain Composition of the Human Hyoglossus Muscle

Abstract: The human tongue muscle hyoglossus (HG) muscle is active in oro-motor behaviors encompassing a wide range of tongue movement speeds. Here we test the hypothesis that the human HG is composed of “uncommon” myosin heavy chain (MHC) isoforms MHCembryonic, MHCneonatal and MHCslow tonic as has been reported for other head and neck muscles active during kinematically diverse behaviors. Following reaction of human HG with antibodies specific for MHCI, MHCIIA, MHCII, MHCembryonic, MHCextraocular, MHCneonatal and MHCsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
(108 reference statements)
1
20
0
Order By: Relevance
“…The findings of an unusually high proportion of hybrid fibres in the intrinsic tongue muscles are generally in line with recent data from studies on human extrinsic tongue muscles, the styloglossus and hyoglossus [Sokoloff et al, 2007[Sokoloff et al, , 2009. Fibres containing multiple MyHC isoforms have been reported to have contractile properties in between those corresponding to the MyHC isoforms they express [Larsson and Moss, 1993;Bottinelli et al, 1994].…”
Section: Discussionsupporting
confidence: 75%
“…The findings of an unusually high proportion of hybrid fibres in the intrinsic tongue muscles are generally in line with recent data from studies on human extrinsic tongue muscles, the styloglossus and hyoglossus [Sokoloff et al, 2007[Sokoloff et al, , 2009. Fibres containing multiple MyHC isoforms have been reported to have contractile properties in between those corresponding to the MyHC isoforms they express [Larsson and Moss, 1993;Bottinelli et al, 1994].…”
Section: Discussionsupporting
confidence: 75%
“…In the human styloglossus and hyoglossus, we previously reported 13-19% MHC-beta-MHC-2x fibers but few MHC-2x fibers (we could not distinguish MHC-2a-MHC-2x fibers [Sokoloff et al, 2007b;Sokoloff et al, 2009]), suggesting that this isoform may be primarily expressed in hybrid fibers. In previous IHC studies of adult human extrinsic tongue muscles, we found limited or no MHC-emb, MHC-eo, MHC-neo and MHC-st [Sokoloff et al, 2007a, b;Sokoloff et al, 2009]. Here, we extend these findings to anterior tongue body muscles.…”
Section: Comparison To Other Tongue Studiesmentioning
confidence: 84%
“…The human MHC-ma gene produces a truncated and nonfunctional protein but is still transcribed in masseter [Stedman et al, 2004]. MHCst is demonstrated by immunohisotochemistry (IHC) in extraocular muscles, but its presence in other head and neck muscles is in dispute Brandon et al, 2003;Sokoloff et al, 2007a;Sokoloff et al, 2009]. To our knowledge, MHC-st has not been studied by PCR, which enables identification of low levels of mRNA expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the human tongue is composed mostly of fast (type II) muscle fibers [27,28,29,30]. Genioglossus and the intrinsic tongue muscles are non-uniform in their spatial distributions of fiber types and sizes in a variety of non-human animals (for review, see [31]) and in humans [27,28,32].…”
Section: Muscular Structure Of the Tonguementioning
confidence: 99%